Contradiç\~oes em processo: Um estudo da estrutura e evoluç\~ao do PRONAF de 2000 A 2010 - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This work aims to understand what implications the process of conservative modernization determined the structure of supply of credit costs and investment of the National Program for Strengthening Family Agriculture (PRONAF) for the period 2000-2010. Therefore, we adopted the descriptive analytical method as a tool to classify and interpret the information contained in the database used in the preparation of the study. Roughly, it is observed that the farmers vis-à-vis the PRONAF B were those who received more resources in the form of credit, whether investment is costing the period 2000-2010, the proceeds from PRONAF. They are farmers who already have some integration to markets, but also have a history in acquiring technological packages. In the case of group PRONAF B, which represents almost 56 % of family farms in Brazil and focuses largely rural poverty, access to credit for investment and funding coming from the PRONAF was narrower. However, it is important that in the states where the predominant public PRONAF B focus, in particular, in the northeastern of Brazil (Bahia, Ceará, Pernambuco, Piauí and Paraíba) and Minas Gerais. These areas concentrate 76% of the total number of beneficiaries of contracts and 76 % of the total values of loans PRONAF category B, but coalesce only 20% of the total number of beneficiaries of contracts and 5 % of the total value of loans. The group PRONAF Family Farmers were found that focuses predominantly in the South (Rio Grande do Sul, Santa Catarina and Paraná) and Minas Gerais. Together these states accounted for 65% of the total number of beneficiaries of contracts and 66 % of the total value of loans category PRONAF Family Farmers. At the national universe, these values were, respectively, just over 44% and almost 55%. Finally, it is emphasized that the policy of granting credit PRONAF is not neutral in its distribution among its beneficiaries, it focuses greatly in the Family Farmers Group vis-à-vis PRONAF B, as well as concentrates, in particular, those regions that already have greater economic dynamism as is the case in the South and Southeast regions.
Keywords: R58; 330; rural development; family farming; PRONAF